PRAKTIK KARTEL HARGA MINYAK GORENG DI INDONESIA - Muhammad Rifqi Arfan Maulana (2023)
The phenomenon of rising prices and scarcity of availability of Cooking Oil in the community has occurred since the end of 2021. The government has taken firm steps by conducting an investigation and naming 27 companies as parties involved in the alleged Cooking Oil price cartel case. The purpose of this study is to analyze the legal consequences of implementing the Cooking Oil price cartel carried out by the 27 companies and to explain the form of legal protection carried out by the government for business actors and consumers who are affected by the practice of the Cooking Oil price cartel in Indonesia. The research in this article was carried out using a normative juridical method with a statute approach and a case approach and was analyzed using qualitative data analysis techniques. The results of the study show that the legal consequences of price cartel practices are sanctions for violating the provisions of Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition and Regulation of the Minister of Trade Number 49 of 2022 concerning Management of the People's Cooking Oil Program. In addition, the government has carried out legal protection by following up on the findings of the KPPU's investigation in court in order to impose sanctions on the reported party who is proven to have violated the provisions of the applicable laws and regulations so that consumers can be freed from business actors who harm consumers, and other business actors can carry out economic activity with healthy competition. Responding to the findings of the alleged cooking oil price cartel, the government should conduct an analysis of related policies in order to prevent legal loopholes that can be exploited by business actors to gain profits in ways prohibited by law.